Retail advertising and promotion - Phau, Ian (Henry Stewart Talks, 2009)
The challenges in retail advertising and promotion, Branding and its implications on customers, The use of advertising and promotion in forming customer relationships, Specific discussion on the design of marketing programs and the alternative marketing tools and strategies